The Influence of Clean and Healthy Behavior Counseling on Students' Knowledge of SDN 211/IV, Jambi City - Fajrina Hidayati; Budi Aswin (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Unhealthy behavior can lead to more serious problems such as the spread of infectious diseases. PHBS in schools includes actions taken by students, teachers, and the community around the school based on awareness of learning outcomes. This study aimed to determine the difference in knowledge before and after being given counseling about PHBS for students at SDN 211/IV Jambi City. This quantitative study uses a true experimental pre-test and post-test control group design approach. The sample in this study was 60 respondents. The data in this study were analyzed using statistical tests, namely the Paired t-test and the Independent t-test. The results showed that the value of students' knowledge about PHBS before being given counseling was an average of 11.94 and the value of students' knowledge about PHBS after being given counseling was an average of 14.58. The results of the t-test showed that there was a difference in the average score between the pre-test and post-test of 2.64 and the value of p = 0.000 (p-value <0.05), meaning that there was a difference in students' knowledge before and after giving health counseling about PHBS in SDN 211/IV Jambi City. This study suggests that schools are encouraged to pay attention to students in terms of Clean and Healthy Behavior (PHBS) by including PHBS points in the material given to students.